Bridging the Digital Divide: Leveraging Lightweight Frontend Architectures for Inclusive Web Access - Vasanth Krishnamoorthy (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the role of lightweight frontend architectures in bridging the digital divide, addressing the challenge of unequal access to web services across the globe. It begins by examining the scope and consequences of the digital divide, highlighting disparities in internet access and device availability. The article then delves into the technical aspects of lightweight frontend architectures, discussing key principles such as performance-aware design and low data consumption techniques. Strategies for implementation, including progressive web apps, localized caching solutions, and minimalistic design, are thoroughly explored. The impact of these approaches on critical services like e-learning platforms, healthcare portals, and government websites is analyzed, supported by case studies demonstrating improved accessibility. Beyond technical solutions, the article considers the broader economic and social implications of increased web accessibility, as well as challenges in large-scale implementation. Finally, it looks towards future directions, discussing emerging technologies, policy implications, and the potential for global collaboration in addressing the digital divide. Throughout, the article emphasizes the transformative potential of lightweight frontend architectures in creating a more inclusive and equitable digital landscape.